2015
DOI: 10.1590/2317-1545v37n1139405
|View full text |Cite
|
Sign up to set email alerts
|

Reduced time for evaluation of the germination test for sunflower seeds

Abstract: Establishing ideal conditions and speed in carrying out the germination test for sunflower seeds is of utmost importance in quality control programs of companies dedicated to the production of high technology seeds. In this regard, the aim of this study was to verify the possibility of reducing the evaluation time of the germination test of sunflower seeds in different substrates and temperatures. Six seed lots of the cultivar Helio 251 and six lots of the cultivar Helio 253 were used. As well as germination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Furthermore, the recommendation to perform the test on paper facilitates fungal dissemination, which may be a problem for species that require a prolonged time to reach the normal seedling standard (Silva et al, 2017;ISTA, 2020). The adoption of a criterion that reduces the duration of the germination test reduces pathogen attacks in seedlings with all necessary structures to be considered normal (Rosa et al, 2010, Caldeira et al, 2015. Some studies were carried out to obtain seed viability in a practical way either by the adequacy of alternative techniques, such as the tetrazolium test (Calles et al, 2020) or by reducing the duration of the germination test or through seed treatments (Caldeira et al, 2015;Tomaz et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the recommendation to perform the test on paper facilitates fungal dissemination, which may be a problem for species that require a prolonged time to reach the normal seedling standard (Silva et al, 2017;ISTA, 2020). The adoption of a criterion that reduces the duration of the germination test reduces pathogen attacks in seedlings with all necessary structures to be considered normal (Rosa et al, 2010, Caldeira et al, 2015. Some studies were carried out to obtain seed viability in a practical way either by the adequacy of alternative techniques, such as the tetrazolium test (Calles et al, 2020) or by reducing the duration of the germination test or through seed treatments (Caldeira et al, 2015;Tomaz et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of a criterion that reduces the duration of the germination test reduces pathogen attacks in seedlings with all necessary structures to be considered normal (Rosa et al, 2010, Caldeira et al, 2015. Some studies were carried out to obtain seed viability in a practical way either by the adequacy of alternative techniques, such as the tetrazolium test (Calles et al, 2020) or by reducing the duration of the germination test or through seed treatments (Caldeira et al, 2015;Tomaz et al, 2016). Although these techniques are effective, some require higher technification of the laboratory and specialized personnel, generating extra costs and making evaluation difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Campos and Tillmann (1997) and Tomaz et al (2010) concluded that it is possible to terminate the germination test for some species with single countings. Caldeira et al (2015) emphasized that there is the possibility of reducing the evaluation period of the germination test on the seventh day after sowing in sand at the temperature of 25 °C.…”
Section: Improvements (Advances) In Testing Processmentioning
confidence: 99%
“…The germination test should be performed in sufficient time to achieve the proposed objectives. Shorter duration of the tests results in lower operational costs and lower risks of proliferation of pathogenic microorganisms (Caldeira et al, 2015;Michelon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%